Designing a Basic Natural Science E-Module: Integrating Eco-Socioscience and Maqasid Shariah for Non-Science Learners - Sukardi Abbas; Abusahman Nasim; Julkarnain Syawal; Indriani Fahri (STAI Hubbulwathan Duri, 2025)
Climate change presents critical challenges to both ecosystems and human well-being, necessitating proactive educational approaches that engage students as future stewards of the environment. A comprehensive understanding that integrates religious, scientific, social, and environmental perspectives is essential to instill moral responsibility in students. This study aimed to develop a Basic Natural Science (BNS) learning module integrated with eco-socioscience and grounded in maqasid sharia principles. The research employed the 4-D development model: Define, Design, Develop, and Disseminate. Six experts—two each in material, design, and language—evaluated the module for validity. Practicality testing was conducted with 31 students. Validation results indicated high feasibility: material experts scored the module at 88.33%, design experts at 92.86%, and language experts at 89.16%, yielding an overall validity score of 90.12%. The practicality test returned an average score of 3.99 (out of 5), confirming the module's applicability in real learning environments. The module effectively integrates eco-socioscience content, such as the ecological and social impacts of pollution, while embedding Islamic ethical teachings. Concepts like stewardship (khalifah) and the prohibition of waste (israf) align environmental responsibility with Islamic values. This fusion promotes environmental awareness rooted in both scientific understanding and religious morality. The BNS module is a valid, practical, and effective educational tool. It successfully fosters environmental literacy and moral consciousness among students through an interdisciplinary and faith-based pedagogical approach.